Hydrogen production via catalytic steam reforming of bio-oil model compounds over NiO-Fe2O3-loaded palygouskite - Wang, Y.; Chen, M.; Liu, Shaomin; Yang, Z.; Shen, C.; Liu, K. (2015)
A series of NiO-Fe2O3 catalysts loaded on palygouskite were prepared by co-precipitation method and used in the catalytic steam reforming to produce hydrogen in a self-made three-stage fixed bed reactor. The loading of NiO-Fe2O3, reaction temperature and ratio of steam to carbon (S/C) on hydrogen production were investigated, with a water-soluble mixture of acetic acid, ethanol and phenol as the bio-oil model compounds. The results indicated that under the optimum conditions, viz., 650 °C, an S/C ratio of 8~10 and 50%NiO-50%Fe2O3/PG as the catalyst, the relative content of H2 reaches 66.15% in the gaseous product.